2010
DOI: 10.1111/j.1582-4934.2009.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irreversibly glycated LDL in human vascular smooth muscle cells: lipid loading, oxidative and inflammatory stress

Abstract: The major complication of diabetes is accelerated atherosclerosis, the progression of which entails complex interactions between the modified low-density lipoproteins (LDL) and the cells of the arterial wall. Advanced glycation end product-modified-LDL (AGE-LDL) that occurs at high rate in diabetes contributes to diabetic atherosclerosis, but the underlying mechanisms are not fully understood. The aim of this study was to assess the direct effect of AGE-LDL on human vascular smooth muscle cells (hSMC) dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 46 publications
2
56
0
1
Order By: Relevance
“…Published data show that oxLDL, but not native LDL, upregulate the expression of NOX4/p22 phox in human macrophages, mediated by MEK1/ERK pathway, upstream messengers of NF-κB signaling, but the upstream components of this signaling mechanism in macrophages have not yet been clearly identified [5]. Our experiments showed that BE inhibits NF-κB in oxLDLloaded macrophages, a signaling pathway responsible for the inhibition of p22 phox and NOX4 expression, similar to the one described in human aortic smooth muscle cells [4]. Unlike the other subunits of Nox complex, NOX1 and NOX2, which demand regulatory subunits for their activation, NOX4 generates ROS constitutively, and changes in its levels may directly affect Nox activity [26].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Published data show that oxLDL, but not native LDL, upregulate the expression of NOX4/p22 phox in human macrophages, mediated by MEK1/ERK pathway, upstream messengers of NF-κB signaling, but the upstream components of this signaling mechanism in macrophages have not yet been clearly identified [5]. Our experiments showed that BE inhibits NF-κB in oxLDLloaded macrophages, a signaling pathway responsible for the inhibition of p22 phox and NOX4 expression, similar to the one described in human aortic smooth muscle cells [4]. Unlike the other subunits of Nox complex, NOX1 and NOX2, which demand regulatory subunits for their activation, NOX4 generates ROS constitutively, and changes in its levels may directly affect Nox activity [26].…”
Section: Discussionmentioning
confidence: 53%
“…The generation of increased intracellular reactive oxygen species (ROS) was associated with oxLDL uptake by macrophages [3]. Moreover, oxLDL is known to induce the expression of NADPH oxidase subunits NOX4/p22 phox and NOX2/p47 phox /p22 phox in human smooth muscle cells [4] and macrophages [5,6], thus generating intracellular oxidative stress. Macrophages are key mediators in the immune response and their physiological protective function is harmfully activated in the atherosclerotic process [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the presence of AGES and glycosylated LDL in the lesion will be detected by RAGE expressed on macrophages and promote inflammation. Thus, the presence of other forms of modified LDL inside atheromas will be enough to justify a dangerous and accelerated evolution of atheromas in people with diabetes, smokers and patients with chronic kidney disease [99,127,128]. Several canonical ligands of TLRs can potentially be present in the lesions and mediate the polarisation of macrophages towards M1 functions.…”
Section: How Risk Factors and Comorbidities Could Cooperate With Ox-lmentioning
confidence: 99%